Alcoholic Beverage Choice – What Matters? - Trasberg, Viktor (Estonian Discussions on Economic Policy, 2019)
The focus of this paper is to identify certain socio-economic factors, which have an impact on alcohol preferences in Estonia. This is important in designing effective alcohol and fiscal policies.The analyses are based on a questionnaire (IARD, Washington DC) administered in the Baltic countries in 2016. The paper brings out relationship between preferences of alcoholic beverages (e.g. beer, wine and strong alcohol) and socio-economic characteristic of those consumers groups.A multinomial logistic regression model allows us to predict the likelihood of a person being allocated to a certain group of consumers of alcoholic beverages.